2020
DOI: 10.1186/s13568-020-00995-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial delivery of the anti-tumor azurin-like protein Laz to glioblastoma cells

Abstract: Salmonella typhimurium VNP-20009 (VNP) is a non-pathogenic attenuated strain, which, as a facultative anaerobe, preferentially accumulates in hypoxic regions of solid tumors. Here, VNP was utilized as a delivery vehicle of the antitumor protein Lipidated azurin, Laz, which is produced by the meningitis-causing bacterium Neisseria meningitides. In brain cancer cells, Laz has been demonstrated to induce apoptosis through an interaction with the tumor suppressor protein p53. In this study, the laz gene, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Likewise, anticancer activity of azurin was demonstrated in vitro in gastrointestinal cancers cell lines [65]. These evidences brought to the investigation on the possible optimization of azurin formulation to improve its efficacy [13,66,67], such as the drug delivery into chitosan nanoparticles [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, anticancer activity of azurin was demonstrated in vitro in gastrointestinal cancers cell lines [65]. These evidences brought to the investigation on the possible optimization of azurin formulation to improve its efficacy [13,66,67], such as the drug delivery into chitosan nanoparticles [65].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, cupredoxins are metalloproteins involved in bacterial electron transport chain [8,9] showing different activities including antimalarial [10] and anticancer ones [5,[11][12][13][14][15]. The cupredoxin family includes azurins, rusticyanins, pseudoazurins, auracyanins, amicyanins, and halocyanins [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed a decrease in toxic side effects on normal tissue cells, while high intratumor concentrations of these apoptosis inducers promoted antitumor activity. Mansour et al, reported a Salmonella enterica expressing anti-tumor protein Lipidated azurin, Laz, that induces apoptosis through an interaction with the tumor suppressor protein p53; this recombinant Salmonella induced apoptosis in vitro models of glioblastoma and breast cancer [ 156 ]. Recently, Mateos Chávez et al, used a Salmonella Typhimurium SL3261 to express and release, via the MisL autotransporter (T5SS), a permeable peptide of the BH3 domain of the pro-apoptotic protein Bax; the administration of this recombinant to a non-Hodgkin lymphoma xenotransplant murine model (NHL) decreased the tumor mass, and increased the mice’s survival.…”
Section: Salmonella Enterica As a Delivery System Of Heterol...mentioning
confidence: 99%
“…Polypeptide Laz crosses the blood-brain barrier during Neisserial infections. However, in this study authors limited their system to express the therapeutic protein Laz at the hypoxic tumor region under hypoxia-induced promoter, HIP-1, selecting Laz upstream for targeting hypoxic tumors [66].…”
Section: Pathogenic Bacteria In Bbctmentioning
confidence: 99%